Correlation and Path Coefficient Analysis of Tomato Germplasms - Rahman, Md. Salehur; Parveen, Shahanaz; Rashid, Md.Harun -Ur-; Akter, Runa; Hossin, Abu Yousuf; Robbani, Md. Golam (International Journal of Applied Sciences and Biotechnology, 2015)
Forty eight genotypes of tomato were evaluated for yield contributing characters to observe their associations and direct and indirect effect on yield. Character association analysis among yield and yield contributing characters revealed that in most of cases the genotypic correlation coefficient was higher than the respective phenotypic correlation coefficients. This indicated that the suppressive effect of the environment modified the phenotypic expression of these characters by reducing phenotypic correlation values. Also, narrow difference between phenotypic and genotypic correlation coefficient was noticed for almost all the pairs of characters studied showing that masking or modifying effects of the environment was little indicating the presence of an inherent association among these characters. Fruit/cluster showed non-significant positive association with yield/plant at genotypic and phenotypic level but individual weight of fruit had significant negative association at phenotypic level with yield/plant. Path coefficient analysis revealed that no. of fruit/cluster had the highest positive direct effects on fruit yield/plant suggesting their importance while imposing selection for correlation of yield in tomato. Int J Appl Sci Biotechnol, Vol 3(2): 223-226 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12421